The Effect Of Blended Learning On Fifth-Grade Students’ Literacy And Numeracy Outcomes - Aji Dwi Priansyah; Jumiati Siska; Lina Tri Astuty Br Sembiring (Universitas Dehasen Bengkulu, 2026)
This study addresses the ongoing challenge of improving literacy and numeracy competencies in Indonesian elementary education, particularly within the implementation of the Merdeka Curriculum. Although numerous studies have examined Blended Learning, limited research has specifically explored the integration of face-to-face instruction and Google Sites–based online learning to strengthen literacy and numeracy skills at the elementary level. This study aims to analyze the effect of Blended Learning on fifth-grade students’ literacy and numeracy learning outcomes.A quantitative approach with a pre-experimental one-group pre-test post-test design was employed. The participants were 26 fifth-grade students at SD Negeri 59 Kota Bengkulu. The research instrument consisted of validated and reliable literacy–numeracy tests. Data were analyzed using the Shapiro–Wilk normality test and paired sample t-test.The findings revealed a significant improvement between pre-test (M = 55.65) and post-test (M = 78.62) scores, with a significance value of < 0.001. The 41.3% increase indicates that Blended Learning effectively enhances students’ literacy and numeracy outcomes. Theoretically, this study contributes to the discourse on technology integration in competency-based learning, while practically offering an innovative instructional strategy aligned with 21st-century learning demands in elementary education.